A Variational Formulation for the Relativistic Klein-Gordon Equation - Botelho, Fabio Silva (Ciência e Natura, 2018)
This article develops a variational formulation for the relativistic Klein-Gordon equation. The main results are obtained through a connection between classical and quantum mechanics. Such a connection is established through the definition of normal field and its relation with the wave function concept.